(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The term “bio stimulants” was actually coined by horticulturists for denoting the various substances which are used for promoting plant growth without being a nutrient or pesticides. In a web journal named Ground Maintenance (http://grounds-mag.com), Zhang and Schmidt from Virginia Polytechnic Institute and State University, defined biostimulants as “materials that, in minute quantities, promote plant growth”.Kauffman et al. (2007) defined biostimilants as ‘materials, other than fertilizers, that promote plant growth when applied in low quantities’. Kauffman et al. (2007) summarized bio stimulants by introducing a categorization: ‘Bio stimulants in a variety of formulations are generally classified into three major groups on the basis of their source and content. These groups include products contain hormone, humic substances and amino acid containing products. Seaweed extracts contain identifiable amounts of active plant growth substances such as auxins, cytokinins, or their derivatives’. Plant bio stimulants, also referred as agricultural bio stimulants, are group of diverse substances which can be supplemented to the close environment of plants and have positive effect on nutrient uptake and plant growth (du Jardin 2012). Although, the application of plant biostimulants in the rhizosphere facilitates nutrient uptake and plant growth, however, many of these plant biostimulants are reported to alleviate abiotic stresses such as salt, drought and heat stresses (Van Oosten et al., 2017).Over the following years, the term ‘biostimulant’ is being increasingly applied by the scientific community and literatures increasing the array of substances and of modes of actions as well (Calvo et al., 2014, du Jardin, 2012). Truth be told, ’biostimulant’ come into view as a flexible descriptor of any substance advantageous to plants excluding fertilizers, pesticides and soil amendments.Industries and Companies in this particular sector have formed many associations, such as ‘European Biostimulants Industry Council’ (EBIC) in Europe and the ‘Biostimulant Coalition’ in the USA, with primary aim to dialogue with scientists, stakeholders and regulators. Study and understanding of biostimulants and their possible effect has been growing at a significant rate (Colla and Roupharl 2015). The effectiveness of biostimulants, exclusively in view with plant growth promotion and nutrient uptake, has been examined (du Jardin 2015; Calvo et al. 2014 ;). In addition to plentiful manuscripts, researchers have extensively reviewed various classes of specific biostimulantsincludingseaweed extracts, humic and fulvic acids, protein hydrolysates, phosphite, silicon, chitosan, PGPRs, Trichoderma, arbuscular mycorrhizal fungi.